Revision of the Australian species of Gonatopus group 5 (Hymenoptera: Dryinidae), with description of a new species from the Society Islands, French Polynesia - Olmi, Massimo; Marletta, Alessandro; Guglielmino, Adalgisa (Zootaxa, 2014)
Eleven Australian species of Gonatopus Ljungh, 1810 group 5 are revised. A new species is described from the Leeward Islands: G. perraulti Olmi, Marletta & Guglielmino, sp. nov. (French Polynesia: Society Islands). New combination is proposed for G. levis (Olmi, 1991), comb. nov. (from Dicondylus). A new key to the Australian species of Gonatopus group 5 is presented.